Current Account, GDP Growth, Terms of Trade and Exchange Rate in Argentina - Güida, Juan José (Cuyonomics. Investigaciones en Economía Regional, 2019)
The article explores the relationship between Argentina’s current account and its likely determinants in the light of macroeconomic and international trade theories. The analysis focuses on three key explanatory variables: the real effective exchangerate, the terms of trade and GDP-growth. The periods considered are the time under the currency board (1991-2001) and that with a flexible exchange rate (2002-2017). The statistical analysis is based on the databases of the IMF, the World Bank and UNCTAD. Results lead to discarding GDP-growth, whereas the real exchange rate and the terms of trade correlate strongly or very strongly with the current account result. As regards causality, the terms of trade seem to exert influence on the real exchange rate, which in turn determines the current account balance. The article does not elaborate on individual balances such as merchandise or services trade, this remaining a matter for further research. Â El artículo explora la relación entre el balance de la cuenta corriente de la Argentina y sus probables determinantes a la luz de las teorías macroeconómicas y del comercio internacional. El análisis se centra en tres variables explicativas: el tipo de cambio real efectivo, los términos del intercambio y el crecimiento del PBI. Se consideran los períodos de la convertibilidad (1991-2001) y del tipo de cambio flexible (2002-2017). El análisis estadístico se basa en datos del FMI, del Banco Mundial y la UNCTAD. Los resultados per miten descartar el crecimiento del PBI, mientras que el tipo de cambio real y los términos del intercambio se correlacionan fuertemente o muy fuertemente con el resultado de la cuenta corriente. Respecto a la causalidad, los términos del intercambio parecen ejercer influencia sobre el tipo de cambio, el que, por su parte, determina el balance de la cuenta corriente. El artículo no profundiza en balances individuales, como el comercio de mercancías o de servicios, lo que requeriría investigación adicional.